2017
DOI: 10.21859/focsci-03021422
|View full text |Cite
|
Sign up to set email alerts
|

Macrosomia and the IGF System: A Short Review

Abstract: Introduction: Macrosomia in diabetic pregnancy is an ubiquitous finding and implies both maternal and fetal issues. Its incidence surpasses other critical obstetrical morbidity in diabetic pregnancy with increased placental size and polyhydramnios as comorbidity. The studies on the underlying factors contributing to macrosomia have focused on growth stimuli like IGF, glycemia, and insulin and their effects on regional organ function. IGF-I and -II in maternal serum are associated with birth weight and the bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…IGF-2 shares structural similarity with IGF-1, exerting antiapoptotic, growth-regulating and mitogenic effects [ 28 ]. IGFs circulate bound to six types of high-affinity proteins (IGFBP 1–6) that regulate their bioavailability and bioactivity through proteolysis and phosphorylation [ 15 , 23 ]. Baldwin et al found an inverse relationship between maternal IGFBP-1 during the second trimester (20–24 weeks) and several fetal dimensions assessed by ultrasound, such as biparietal diameter, abdominal circumference, femur length, tibia length and subcutaneous fat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-2 shares structural similarity with IGF-1, exerting antiapoptotic, growth-regulating and mitogenic effects [ 28 ]. IGFs circulate bound to six types of high-affinity proteins (IGFBP 1–6) that regulate their bioavailability and bioactivity through proteolysis and phosphorylation [ 15 , 23 ]. Baldwin et al found an inverse relationship between maternal IGFBP-1 during the second trimester (20–24 weeks) and several fetal dimensions assessed by ultrasound, such as biparietal diameter, abdominal circumference, femur length, tibia length and subcutaneous fat.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, peptide YY inhibits food intake and weight gain and opposes the effects of ghrelin on food intake and energy balance [ 19 , 20 ]. The incretin hormones, glucagon-like peptide-1 (GLP-1) and insulin-like growth factors 1 and 2 (IGF-1 and -2), generally have anorectic properties [ 15 , 21 , 22 , 23 ]. Finally, leptin (the main anorectic hormone) released by adipocytes when fat stores are in excess [ 16 , 24 ], inhibits food intake and regulates nutrient uptake [ 25 ].…”
Section: Introductionmentioning
confidence: 99%